2020
DOI: 10.1093/nar/gkaa934
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and development of novel DNA-PK inhibitors by targeting the unique Ku–DNA interaction

Abstract: DNA-dependent protein kinase (DNA-PK) plays a critical role in the non-homologous end joining (NHEJ) repair pathway and the DNA damage response (DDR). DNA-PK has therefore been pursued for the development of anti-cancer therapeutics in combination with ionizing radiation (IR). We report the discovery of a new class of DNA-PK inhibitors that act via a novel mechanism of action, inhibition of the Ku–DNA interaction. We have developed a series of highly potent and specific Ku–DNA binding inhibitors (Ku-DBi’s) tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 54 publications
0
27
0
Order By: Relevance
“…Weterings et al identified several potential inhibitors by computational screening and characterized a low micro-molar inhibitor that disrupts the binding of Ku70/80 to DNA substrates [ 55 ]. Recently, Gavande et al described the discovery of highly potent and selective DNA-PK inhibitors that block the Ku70/80 heterodimer interaction with DNA [ 56 ] ( Figure 3 f).…”
Section: Regulation Of Ku Activities By Small Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…Weterings et al identified several potential inhibitors by computational screening and characterized a low micro-molar inhibitor that disrupts the binding of Ku70/80 to DNA substrates [ 55 ]. Recently, Gavande et al described the discovery of highly potent and selective DNA-PK inhibitors that block the Ku70/80 heterodimer interaction with DNA [ 56 ] ( Figure 3 f).…”
Section: Regulation Of Ku Activities By Small Moleculesmentioning
confidence: 99%
“…The loops of Ku in contact with DNA superimpose well, indicating that Ku has the same inner ring conformation with or without DNA-PKcs. ( f ) Inhibitors of Ku-DNA interactions reported by [ 55 ] (compound L) and by [ 56 ] (compound 245).…”
Section: Figurementioning
confidence: 99%
“…Small molecule inhibitors have been developed that target the first step in the NHEJ pathway, namely binding of Ku70/80 dimer to DNA ( Figure 3B ; Weterings et al, 2016 ; Gavande et al, 2020 ). The most promising inhibitors target a ligand binding pocket in close proximity to the DNA-binding region, interfacing with both the Ku70 and Ku80 subunit.…”
Section: Combination Therapiesmentioning
confidence: 99%
“…The most promising inhibitors target a ligand binding pocket in close proximity to the DNA-binding region, interfacing with both the Ku70 and Ku80 subunit. By blocking the DNA binding capacity of the Ku heterodimer, the downstream catalytic activity of DNA-PKcs is inhibited, hereby preventing DSB repair ( Weterings et al, 2016 ; Gavande et al, 2020 ). The inhibitors induce increased sensitivity to DSB inducing agents, such as IR, in in vitro experiments.…”
Section: Combination Therapiesmentioning
confidence: 99%
“…NHEJ is the predominant and fast-acting pathway to repair CRISPR-mediated DSBs and outcompetes other editings [24,33]. Therefore, NHEJ inhibitors improve HDR efficiency [34][35][36]. One of the most effective NHEJ inhibitors is M3814, which strikingly improves HDR by blocking NHEJ [24,37].…”
Section: The Combination Of M3814 and Trichostatin A Increases Intron-targeting Hdr Editing Efficienciesmentioning
confidence: 99%